Numerical simulation of mutual influence in 470 sailing hull and rudder at different hull speeds - Lin, S.; Ma, Y.; Zheng, W.; Pan, Z. (Proceedings, 2020)
A 470 sailing race requires effective cooperation between athletes to optimize the hull position and the correct heading. To understand the effect of the hull on the maneuverability of the rudder and the influence of the rudder on the stability and rapidity of the hull at different ship speeds, requires numerical 3D simulation and research on the viscous flow field of 470 sailing based on Reynolds-averaged Navier-Stokes equations. The results show that the rudder can reduce the wave making characteristics of the hull, reducing energy loss and thus improving the hull`s rapidity when the speed is greater than 6 m/s, as the effective area of rudder decrease and increases the stall angle, which reduces the manipulatable performance of the rudder to some extent. This study could quantify the performance of the hull and rudder at different speeds. Moreover, this study might provide strategies for the athletes to effectively control the rudder and hull at different speeds.